INFLUENCE OF TECHNOLOGICAL FACTORS ON OIL RECOVERY FROM OIL RIMS - Zakirov S.N.; Severov Ya.A. (My University, 2006)
Russia’s oil resources that open onto oil rims make up approximately one-third of the total reserves. They are characterized as hardly recoverable deposits. The coefficient of oil recovery (COR) is an integral indicator of the efficiency of oil recovery from a productive bed. The COR in oil rims is usually characterized by low values (20% or less). A significant number of researches dedicated to the systems of oil rim development and methods of increasing the efficiency of oil recovery from the rims has been performed in Russia and abroad.